Haematological and molecular characterisation of high haemoglobin F among anaemic patients in Hospital Universiti Sains Malaysia - Ghani, Siti Nor Assyuhada Mat (2020)
Anaemia is a condition usually associated with variety of diseases. In normal adults, haemoglobin F (HbF) levels are usually less than 1.0%. There are several genetic loci that have significant influence on HbF levels. The aim of this study is to determine the association between elevated HbF level with haematological parameters and the presence of the BCL11A (rs1186868) and HMIP-2 (rs9376090) SNPs in anaemic patients due to acquired causes. This study involved 144 anaemic patients from Hospital Universiti Sains Malaysia (HUSM) with HbF level > 1.0%. High-performance liquid chromatography (HPLC) was used to determine the HbF and HbA2 levels. Multiplex ARMS-PCR and gap-PCR were performed for those samples with high HbA2 level (>3.2%) and normal HbA2 level (≤3.2%) respectively to detect mutation at β-globin gene cluster. Allelic discrimination for rs1186868 and rs9376090 were performed using real-time PCR technique for samples with no mutation detected. In this study, the mean age of patients is 19.99 ± 1.64 years with female 61.1% predominance. Majority were Malays (99.3%). There was a moderate negative correlation and statistically significant between HbF level with Hb level and RBC count, (r = -0.348, P < 0.05) (r = -0.377, P < 0.05) respectively. Meanwhile, the correlation between HbF level with MCV and MCH showed weak negative correlation but not statistically significant, (r = -0.079, P > 0.05) (r = -0.073, P > 0.05) respectively. Following multiplex ARMS-PCR, 65 (74.7%) mutations were detected which comprises of 49 heterozygous Cd 26 (75.4%), 10 heterozygous Cd 41/42 (15.4%), 3 compound heterozygous Cd 26 and Cd 41/42 (4.6%) and 3 heterozygous IVS 1–1 (4.6%), while 22 patients were not detected. Out of 57 samples, only one patient (1.8%) was found positive with Thai (δβ)°-thalassaemia type deletions when subjected to the multiplex gap-PCR consisted of four target deletions; Siriraj J Gγ(Aγδβ)o-thal, Thai (δβ)°-thalassaemia, HPFH-6, and Hb Lepore. There was a significant difference between the mean of HbF level of patients with and without β-globin gene cluster mutation and deletion (P < 0.05). The minor allele frequency (MAF) in both rs1186868 and rs9376090 shows similar to the East Asian (EAS) population. There is no significant difference of HbF level between genotypes containing HbF-promoting alleles of rs9376090 (TC and CC) when compared to genotype TT (P > 0.05). In conclusion, HbF level correlates with anaemic status of the subjects. Elevated HbF levels showed associations with both inherited and acquired causes. Additionally, there is no relationship between the increased HbF levels with the presence of SNPs rs9376090-C among acquired anaemic patients. Despite the need for further research in this area, this study provides data that can be used as a guideline for better anaemia treatment and management.